Women Participation in Succession Planning Beyond Organizational Barriers and Personal Bias: A Study of Domestic Airline Operators in Nigeria - Okolie, Ugo Chucks; Ivwighren, Hannah Emuobosa (Magister Manajemen Universitas Muhammadiyah Sumatera Utara, 2023)
This study examines how women in the workforce participate in succession planning in Domestic Airline Operators in Nigeria under the supervision of the Nigerian Civil Aviation Authority. The Social Action theory was chosen as the study's theoretical foundation and 273 respondents was chosen for this study using random and purposeful sampling methods. The use of questionnaires allowed for the collection of quantitative data. The findings of study revealed that the distribution of strategic duties, employees’ promotion, and other forms of organizational segregation, however, all display gender inequality. Working with seasoned employees who have a track record of success without gender discrimination, as well as understanding the key principles of an effective succession planning and management initiative, can make succession planning a simple and time-saving process. As a result of the findings among others, the government should focus more on passing efficient laws that will support women's empowerment and equity among Nigeria's Domestic Airline Operators.